2021
DOI: 10.1111/tpj.15551
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid kinetic and constraint‐based model of leaf metabolism allows predictions of metabolic fluxes in different environments

Abstract: SUMMARY While flux balance analysis (FBA) provides a framework for predicting steady‐state leaf metabolic network fluxes, it does not readily capture the response to environmental variables without being coupled to other modelling formulations. To address this, we coupled an FBA model of 903 reactions of soybean (Glycine max) leaf metabolism with e‐photosynthesis, a dynamic model that captures the kinetics of 126 reactions of photosynthesis and associated chloroplast carbon metabolism. Successful coupling was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 104 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…To extract useful information from large amounts of ’omics data, computational modeling approaches are increasingly important (Shameer et al ., 2018; Chomthong & Griffiths, 2020; Burgos et al ., 2022). With the methods of model integration we developed previously (Kannan et al ., 2019; Shameer et al ., 2022), our CAM model has the potential to interface with transcriptome data, gene regulatory networks and metabolic models based on flux balance analysis (Cheung et al ., 2014; Shameer et al ., 2018; Töpfer et al ., 2020). This will enable the exploration and assessment of the potential of CAM crops of varying forms in a more comprehensive way, identifying potential targets for yield improvement and contributing to CAM biodesign.…”
Section: Discussionmentioning
confidence: 99%
“…To extract useful information from large amounts of ’omics data, computational modeling approaches are increasingly important (Shameer et al ., 2018; Chomthong & Griffiths, 2020; Burgos et al ., 2022). With the methods of model integration we developed previously (Kannan et al ., 2019; Shameer et al ., 2022), our CAM model has the potential to interface with transcriptome data, gene regulatory networks and metabolic models based on flux balance analysis (Cheung et al ., 2014; Shameer et al ., 2018; Töpfer et al ., 2020). This will enable the exploration and assessment of the potential of CAM crops of varying forms in a more comprehensive way, identifying potential targets for yield improvement and contributing to CAM biodesign.…”
Section: Discussionmentioning
confidence: 99%
“…However, classic FBA does not account for regulatory mechanisms like feedback inhibition or potential metabolite toxicity ( Knoop and Steuer, 2015 ). It could be helpful for future studies to test FSEOF in combination with dynamic extensions of FBA ( Mahadevan et al., 2002 ) and hybrid kinetic and constraint-based models ( Shameer et al., 2022 ). The incorporation of metabolite concentrations, flux rates or kinetic parameters could drastically improve the precision and reliability of the results ( Mahadevan et al., 2002 ; Moulin et al., 2021 ; Shameer et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It could be helpful for future studies to test FSEOF in combination with dynamic extensions of FBA ( Mahadevan et al., 2002 ) and hybrid kinetic and constraint-based models ( Shameer et al., 2022 ). The incorporation of metabolite concentrations, flux rates or kinetic parameters could drastically improve the precision and reliability of the results ( Mahadevan et al., 2002 ; Moulin et al., 2021 ; Shameer et al., 2022 ). For future studies we suggest the combinatorial expression of the identified amplification targets, especially with the native sqs , since it seems to be the rate limiting enzyme in the present study, as well as the combination of amplification and knock-down targets.…”
Section: Discussionmentioning
confidence: 99%
“…Some system-level kinetic models have been developed e.g., (Klipp, 2007;Bordbar et al, 2015;Jamei, 2016), but they usually tend to account for the activity of significantly fewer genes than COBRA models due to a lack of detailed kinetic data for all cellular processes. There have been many methods developed that use Bayesian parameter estimation to predict reasonable thermodynamic and kinetic values to constrain COBRA models e.g., (Liebermeister and Klipp, 2006a;Liebermeister and Klipp, 2006b;Stanford et al, 2013) and subsequently there have been a number of attempts to add kinetic information to FBA models (e.g., (Jamshidi and Palsson, 2008;Adadi et al, 2012;Stanford et al, 2013;Chowdhury et al, 2015;Pozo et al, 2015;Khodayari and Maranas, 2016;Sánchez et al, 2017;Shameer et al, 2022)). Despite this progress, currently the vast majority of FBA models do not contain kinetic information.…”
Section: Whole-cell Modelsmentioning
confidence: 99%